Legal Discipline-(s) - Liendo Tagle, Fernando (EUNOMÍA. Revista en Cultura de la Legalidad, 2022)
In this paper I provide a synthesis of the central issues concerning legal disciplines as objects of knowledge. First, I will point out the lack of semantic and conceptual precision in the uses of the term ‹‹discipline›› when it is equated with an area or speciality of law. I will then move on to place the discipline in historical perspective, which implies examining law as an intellectual tradition that changes over time and develops in relation to accumulated knowledge. Finally, I will present some possible theorisations of legal disciplines, the sources for their study and the dynamics that can be found in their development and formation.